2002
DOI: 10.1063/1.1495896
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond laser ablation of dental enamel

Abstract: Laser ablation of dental enamel with subpicosecond laser pulses has been studied over the intensity range of (0.1-1.4)ϫ10 14 W/cm 2 using 95 and 150 fs pulses at a pulse repetition rate of 1 kHz. The experimentally determined ablation threshold of 2.2Ϯ0.1 J/cm 2 was in good agreement with theoretical predictions based on an electrostatic ablation model. The ablation rate increased linearly with the laser fluence for up to 15 times the ablation threshold. The absence of collateral damage was observed using opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 19 publications
1
47
1
1
Order By: Relevance
“…A recent study has shown that an USPL system that can make clean and precise cuts in the human cornea [41]. Feasibility studies for dentistry, bone drilling, and neurosurgery have also been carried out [43][44][45].…”
Section: Ultrashort Pulse Laser Ablationmentioning
confidence: 99%
“…A recent study has shown that an USPL system that can make clean and precise cuts in the human cornea [41]. Feasibility studies for dentistry, bone drilling, and neurosurgery have also been carried out [43][44][45].…”
Section: Ultrashort Pulse Laser Ablationmentioning
confidence: 99%
“…First, for clinical use, the dentists to whom we have spoken seek a relatively economical, easilyoperated laser for which there is an optical fibre delivery system. Femtosecond lasers do not meet these requirements, although they ablate enamel and dentine with precision and cause minimal thermal or mechanical damage (Kruger et al 1999, Rode et al 2002, Serafetinides et al 1996, Neev et al 1996. Secondly, if the laser is to be cost-effective, some dentists would like to use the laser for other standard treatments like soft tissue surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These ablation characteristics allow for extremely precise tissue removal with minimal damage to the surrounding tissue. Substantial research efforts over the last two decades have explored tissue ablation in the corneal stroma [3][4][5], cortical parenchyma [6], and epidermis [7], and harder tissue like nail [8] and dentin [9][10][11]. These studies led to the first clinical use of ultrafast lasers in laser assisted in situ keratomileusis (LASIK) for flap creation [3] and more recently for cataract surgery [12].…”
Section: Introductionmentioning
confidence: 99%